Emerging concern of supportive supervision in hospital waste management: A formative delphi study - Markus Kaban; Suhartono Suhartono; Purwanto Adhi Pireno; Alberta Widya Kristanti; Perigrinus Hermin Sebong (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Improper management of all types of hospital waste has become a significant problem relevant to public health issues. However, even though there are regulations regarding waste management, the implementation still varies between hospitals. The most neglected factor is the waste management supervision frameworks. Purpose: To identify the emerging concern of supportive supervision in hospital waste management. Method: This formative delphi study employed qualitative methods and focus group discussions (FGDs). Each FGD lasted 60 minutes. The study incorporated the concept of stakeholder engagement in hospital waste governance, focusing on factors driving stakeholder participation, knowledge-sharing structures, information exchange, decision-making processes, and the institutionalization of various centers of power and decision-making to diversify waste management oversight. Results: Participants were most likely to decide to improve waste management. Of the 18 questions, three received a higher number of